2019
DOI: 10.11152/mu-2038
|View full text |Cite
|
Sign up to set email alerts
|

Ankle involvement in rheumatoid arthritis – a comparison of inflammatory signs on musculoskeletal ultrasound and magnetic resonance imaging

Abstract: Aim: To evaluate the frequency of tibiotalar and subtalar joints together with extensor, flexor and peroneal tendons inflammatory lesions in rheumatoid arthritis (RA) patients by using ultrasound (US) and magnetic resonance imaging (MRI).Material and methods. Fifty RA patients and 25 healthy subjects were prospectively included. All patients and controlsunderwent clinical examination (to screen for swollen and/or tender ankles) and ankle US and MRI (to screen for synovialhypertrophy – SH, tenosynovitis and pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…This might explain why we found less ST synovitis visible from the lateral approach in patients with hindfoot valgus. The presence of synovitis could be an important source of pain ( 34 , 35 ) , and probably for this reason the patients had modified walking/standing heel pressure by avoiding heel support (we found that the pressure on the anterior foot in these patients was increased, data not shown). In a 20-year follow-up study, Belt et al .…”
Section: Discussionmentioning
confidence: 80%
“…This might explain why we found less ST synovitis visible from the lateral approach in patients with hindfoot valgus. The presence of synovitis could be an important source of pain ( 34 , 35 ) , and probably for this reason the patients had modified walking/standing heel pressure by avoiding heel support (we found that the pressure on the anterior foot in these patients was increased, data not shown). In a 20-year follow-up study, Belt et al .…”
Section: Discussionmentioning
confidence: 80%
“…A study conducted in 2019 reported that US is an accurate and reliable tool in detecting shoulder pathologies [ 20 ]. Luminița and his colleagues provided the same conclusion about the ankle [ 21 ]. Thus, US may play an important role in the initial imaging modality of the knee in patients with RA.…”
Section: Discussionmentioning
confidence: 77%
“…Although musculoskeletal ultrasound is less sensitive than MRI and X-ray in early detection of synovitis and tenosynovitis [ 24 ], it is suitable for short-term evaluation of stable rheumatic diseases, offering highly accessible, low-cost, real-time imaging without radiation [ 25 , 26 ]. The OMERACT Ultrasound Working Group has engaged in the validation of ultrasound as an outcome measurement instrument (OMI) by defining ultrasound manifestations of spondyloarthritis (SpA) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%